PENDAMPINGAN SANTRI PESANTREN AN-NUUR TAMANSARI SETU DALAM PENINGKATAN KOMPENTENSI DI BIDANG WIRAUSAHA MANDIRI BERBASIS INTERNET - Andi Arfian; Nicodias Palasara; Adelia Alvi Yana; Cepy Unar (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2022)
The digital divide is one of the problems that arise as a result of the development of information technology caused by the gap between society and information technology which is influenced by several factors, including differences in access rights to existing information technology, as happened to students living in Islamic boarding schools. An-Annur Islamic Boarding School, where Islamic boarding schools severely limit students' access to the Internet. This phenomenon is of concern to find out a description of the use of the digital economy among students at the An-Nuur Islamic Boarding School. consists of motivation, physical and material access, skills, and utilization of information technology. This service uses the Workshop method, with the object of research being the An-Nuur Islamic boarding school in Setu District, Bekasi Regency. with the number of participants as many as 30 students and teachers from the results of interviews and workshops obtained there are still many participants who are still new to the use of the digital economy, all of them already understand about online shopping but do not understand how to join an online store and this socialization is beneficial for participants so that they are a little Knowing about the digital economy and the results of this service, it is hoped that the students can become Entrepreneurship in the use of the internet and the use of the digital economy